2009
DOI: 10.1302/0301-620x.91b8.21824
|View full text |Cite
|
Sign up to set email alerts
|

An overview of autologous chondrocyte implantation

Abstract: Chondral damage to the knee is common and, if left untreated, can proceed to degenerative osteoarthritis. In symptomatic patients established methods of management rely on the formation of fibrocartilage which has poor resistance to shear forces. The formation of hyaline or hyaline-like cartilage may be induced by implanting autologous, cultured chondrocytes into the chondral or osteochondral defect. Autologous chondrocyte implantation may be used for full-thickness chondral or osteochondral injuries which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 48 publications
1
90
0
3
Order By: Relevance
“…One major limitation for cell-based therapeutic approaches in articular cartilage regeneration is the lack of sufficient numbers of differentiated HAC at the time of implantation (Gikas et al, 2009). Bone marrow-derived MSC represent an alternative providing that their default hypertrophic pathway could be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…One major limitation for cell-based therapeutic approaches in articular cartilage regeneration is the lack of sufficient numbers of differentiated HAC at the time of implantation (Gikas et al, 2009). Bone marrow-derived MSC represent an alternative providing that their default hypertrophic pathway could be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…The same behavior was observed in ASCs co-culture pellets (data not shown). Pellet cell number evaluation revealed that, starting from 4x10 5 (Fig. 2a).…”
Section: Quantification Ofgags and Dna Contentmentioning
confidence: 99%
“…Conversely, MFx is known to be less effective in patients with larger chondral lesions (2-4 cm 2 ) or early osteoarthritis [13]. In the knee and talus, large chondral defects are successfully treated with autologous chondrocyte implantation (ACI) or matrix-associated autologous chondrocyte implantation (MACI) [14][15][16][17][18][19][20][21][22]. ACI has also been effectively used in the hip.…”
Section: Introductionmentioning
confidence: 99%